The moderating effect of self-control in the relationship between parenting practices and the abstinence of sexual activity among adolescents / Yusma Amira Muhd Yusof - Muhd Yusof, Yusma Amira (2016)
As the nation approaches the year 2020 and with real challenges of globalization, Malaysia needs to have a continuous supply of strong, competent and resilient human capital. These efforts are however impeded by various predicaments especially in the development of younger generations. One of the impediments is the act of delinquency especially pre-marital relationships among the adolescents which were statistically proven to devastate human values and competencies in many ways. This study aims to explore sexual abstinence as a means to help reduce the obstacles in producing sound human capital. This study was based on Information Motivation Behavioral Skills Theory and Attachment Theory. A cross sectional approach was adopted and a total of 338 respondents between the age of 18 and 19 were selected using a combination of stratified and convenient samplings. A printed questionnaire adapted from five different constructs was administered. Logistic regression analyses were performed to justify the relative contributions of three predictors namely; parental monitoring, communication and psychological control. The observe group and predicted probabilities graph successfully predicted the value of 1 (sexual abstinence) as the representation of the characteristics of the study. Only Blaming Attitude dimension of the psychological control was found to be statistically significant. All three dimensions of the moderation (Self Control) were significant. A total of 76% of respondents were found to practice abstinence. The study has found gaps in both theories in which culture and belief system was found to be very important among Malay Muslim respondents. A novel contribution of this study to the body of knowledge is the significant nature of psychological control in maintaining sexual abstinence. The study sees that the government ought to reemphasis the needs to implement all the initiatives highlighted under the National Family Policy earmarked to upgrade and strengthen parenting knowledge and skills.